Capacity building for ACM: Lessons learned from training in distinct contexts - Cronkleton, P.; Evans, K.; Larson, A.M. (Routledge, 2021)
Capacity building should be an integral component of adaptive collaborative management (ACM) approaches to give participants the skills, awareness, and confidence to understand and implement ACM methods. This chapter examines our insights from 20 years of work in ACM by looking at three cases from Bolivia, Nicaragua, and Ghana in which we introduced ACM methods in distinct contexts to assist local stakeholders in addressing forest management challenges. In each case, an initial capacity-building phase was necessary to facilitate ACM processes. We argue that training should be approached through an ACM lens to generate social learning processes, placing experimentation and reflexivity at the core of such capacity-building programmes. Training in ACM is not simply about teaching a new methodology, it is about building an ethos of experimentation, learning and collaboration. Our goal in training was to create self-reinforcing cycles in which participants reflected on their learning so that they could consciously facilitate learning with others. This not only allowed us to gauge the effectiveness of the capacity-building exercises and whether key messages were being captured by trainees, but also to successfully introduce the ACM approach to ongoing initiatives.